Прогнозирование конъюнктуры рынка интернет-услуг в условиях неполной информации (Путеводитель предпринимателя, 2020)
The problem of forecasting of indicators of market condition of Internet-services in the conditions of the incomplete and irregular retrospective information is formulated. The expediency of application local regression models for extrapolation of an economic time number is shown.